Identity on Private Universities’ Billboards in Yogyakarta - Irene Santika Vidiadari (MediaTor (Jurnal Komunikasi), 2020)
This research discusses identity as the visual means of private universities to attract prospective students. The data was collected by documenting billboard advertisements located on the arterial road of the City of Yogyakarta that contain visual and linguistic aspects. The gathered data are four billboards of private universities. Applying the multimodal analysis of Gunther Kress and Theo van Leeuwen, this study examines the billboard text to understand the visual and linguistic aspects as well as the relation between them to construct the commodification of education discourses. This research has found that identity becomes a highlighted aspect of the billboards of private universities. The visualization of the identity appears as on physical characters and attributes wore by the students or the models. There are three identities generally appearing, (1) university identity, through the alma mater jacket; (2) tribal/ethnic identity, through the physical appearance of the models; and (3) religious identity, through the fashion style. The slogans—e.g. ‘Welcome, the Smart and Humanist Generation’ and Excellent, Inclusive, Humanist, [with] Integrity’—written on the billboards, from the perspective of linguistic, represent the ideology of the educational institutions. The slogan is not only an enhancer but also a means to build and modify the meaning of the advertisement.  Furthermore, it also becomes the representation of what kind of higher-education services are offered by the institution. The modification of the message through identity issues shows exclusivity, while the cultural identity indicates the inclusivity on the campus.